Jordanian University Instructors’ Practices and Perceptions of Online Testing in the COVID-19 Era - Haider, Ahmad S.; Hussein, Riyad F.; Saed, Hadeel A. (Frontiers in Education, 2022)
It is widely known that exceptional circumstances inevitably call for the use of matching procedures. As there has been a change in face-to-face teaching methods, there have also been parallel changes in student evaluation and assessment plans or strategies during the COVID-19 era. This study investigates how COVID-19 affected online testing in higher education institutions in Jordan. For this purpose, the researchers developed a five-construct Likert-type questionnaire with 20 items and distributed it to a sample of 426 university instructors. The constructs were the internet and technology, technical and logistic issues, types of questions, test design, and Students' awareness. The results showed that the Internet and technology are essential to guarantee the successful performance of online testing. The study also showed that this type of testing affected the test design and types of questions in a way to eliminate or at least reduce the spread of online cheating. The study recommends that higher education institutions provide instructors with on-the-job training, not only in e-learning techniques and procedures but also in preparing and conducting online exams.